STRATEGI PENINGKATAN SISTEM DELIVERY GRABFOOD DALAM MENINGKATKAN EFISIENSI - Shofi, Fadhoilus; Ammaridho, Evan Andarianto; Putra, Hasannudin Nursalim (Mount Hope Management International Journal, 2024)
This study aims to analyze strategies for improving the GrabFood delivery system to increase efficiency and customer satisfaction in Surabaya City. A qualitative approach with a case study type was used to explore the dynamics of the GrabFood delivery system and identify key factors that influence efficiency and customer satisfaction. Data were collected through interviews with driver partners, customers, and GrabFood management, participant observation, and documentation studies. The results showed that the efficiency of the GrabFood delivery system is influenced by internal factors, such as routing algorithms and driver performance, as well as external factors, such as traffic conditions and weather. GrabFood has implemented strategies to improve efficiency, including route optimization with advanced algorithms and training programs for driver partners. GrabFood customer satisfaction is influenced by factors such as delivery speed, order accuracy, driver friendliness, and food condition. GrabFood continues to strive to improve customer satisfaction by implementing delivery time standards, digital ordering systems, service ethics training, and collaborating with merchants to maintain food quality. SWOT analysis shows that GrabFood has strengths in terms of brand awareness, partner networks, and technology, but also has weaknesses and threats that need to be anticipated.